3D Synaptic Organization of the Rat CA1 and Alterations Induced by Cocaine Self-Administration. (30th November 2020) - Blazquez-Llorca, L; Miguéns, M; Montero-Crespo, M; Selvas, A; Gonzalez-Soriano, J; Ambrosio, E; DeFelipe, J
Abstract: The hippocampus plays a key role in contextual conditioning and has been proposed as an important component of the cocaine addiction brain circuit. To gain knowledge about cocaine-induced alterations in this circuit, we used focused ion beam milling/scanning electron microscopy to reveal and quantify the three-dimensional synaptic organization of the neuropil of the stratum radiatum of the rat CA1, under normal circumstances and after cocaine-self administration (SA). Most synapses are asymmetric (excitatory), macular-shaped, and in contact with dendritic spine heads. After cocaine-SA, the size and the complexity of the shape of both asymmetric and symmetric (inhibitory) synapses increased but no changes were observed in the synaptic density. This work constitutes the first detailed report on the 3D synaptic organization in the stratum radiatum of the CA1 field of cocaine-SA rats. Our data contribute to the elucidation of the normal and altered synaptic organization of the hippocampus, which is crucial for better understanding the neurobiological mechanisms underlying cocaine addiction.